Solidificação da liga de alumínio 319 conformada por spray - Otani, Lucas Barcelos (2017)
The main application of 319 aluminum alloy is for manufacturing components for automobile industry. One of the main concerns related to the recycling of this metal is regarding the incorporation of impurities as iron, for instance. Due to its low solubility in solid aluminum, the presence of this element leads to the formation of intermetallic compounds such as α-Al8Fe2Si and β-Al9Fe2Si2, the most common iron phases in Si-containing Al-alloys. The β phase is harmful to mechanical properties because of its platelet like morphology. Spray forming is an advanced processing technique which can mitigate the deleterious effect of these intermetallic phases. However, the solidification process of spray formed metals is still an open discussion. In these sense, the aim of this work is to contribute to a better understanding of the solidification process of spray formed 319 aluminum alloy. The work was divided in three stages: the first evaluated the presence and morphology of intermetallic phases by varying the pouring temperature and Fe content (0.6 and 1.2 in mass percent); the second evaluated the eutectic Al-Si morphology through varying the processing conditions; and finally, the third evaluated the solute distribution in the final microstructure, in this case other aluminum alloys were studied together with the 319 (2024 and 7050). The basis for discussion the phenomena was a solidification model for spray formed metals recently proposed in the literature, which defines the process in two stages, being the final solidification occurring at low cooling rate. The results showed that by controlling the processing parameters it is possible to mitigate the β-Al9Fe2Si2 formation, as well as to alter the eutectic Al-Si morphology. The third stage indicated the possibility of maintenance of certain solute in solid solution on the periphery of aluminum grains. It could be concluded that the solidification model was adequate to explain the phenomena presented in this work.